High seroprevalence of Leishmania infantum is linked to immune activation in people with HIV: a two-stage cross-sectional study in Bahia, Brazil - de Moraes, Laise; Santos, Luciane Amorim; Arruda, Liã Bárbara; Silva, Maria da Purificação Pereira da; Silva, Márcio de Oliveira; Silva, José Adriano Góes; Ramos, André; Santos, Marcos Bastos dos; Torres, Felipe Guimarães; Orge, Cibele; Teixeira, Antonio Marcos dos Santos; Vieira, Thiago Santos; et al. (Frontiers in Microbiology, 2023)
Visceral leishmaniasis is an opportunistic disease in HIV-1 infected individuals, unrecognized as a determining factor for AIDS diagnosis. The growing geographical overlap of HIV-1 and Leishmania infections is an emerging challenge worldwide, as co-infection increases morbidity and mortality for both infections. Here, we determined the prevalence of people living with HIV (PWH) with a previous or ongoing infection by Leishmania infantum and investigated the virological and immunological factors associated with co-infection. We adopted a two-stage cross-sectional cohort (CSC) design (CSC-I, n=5,346 and CSC-II, n=317) of treatment-naïve HIV-1-infected individuals in Bahia, Brazil. In CSC-I, samples collected between 1998 and 2013 were used for serological screening for leishmaniasis by an in-house Enzyme-Linked Immunosorbent Assay (ELISA) with SLA (Soluble Leishmania infantum Antigen), resulting in a prevalence of previous or ongoing infection of 16.27%. Next, 317 PWH were prospectively recruited from July 2014 to December 2015 with the collection of sociodemographic and clinical data. Serological validation by two different immunoassays confirmed a prevalence of 15.46% and 8.20% by anti-SLA, and anti-HSP70 serology, respectively, whereas 4.73% were double-positive (DP). Stratification of these 317 individuals in DP and double-negative (DN) revealed a significant reduction of CD4+ counts and CD4+/CD8+ ratios and a tendency of increased viral load in the DP group, as compared to DN. No statistical differences in HIV-1 subtype distribution were observed between the two groups. However, we found a significant increase of CXCL10 (p=0.0076) and a tendency of increased CXCL9 (p=0.061) in individuals with DP serology, demonstrating intensified immune activation in this group. These findings were corroborated at the transcriptome level in independent Leishmania- and HIV-1-infected cohorts (Swiss HIV Cohort and Piaui Northeast Brazil Cohort), indicating that CXCL10 transcripts are shared by the IFN-dominated immune activation gene signatures of both pathogens and positively correlated to viral load in untreated PWH. This study demonstrated a high prevalence of PWH with L. infantum seropositivity in Bahia, Brazil, linked to IFN-mediated immune activation and a significant decrease in CD4+ levels. Our results highlight the urgent need to increase awareness and define public health strategies for the management and prevention of HIV-1 and L. infantum co-infection.